Effects of epidural analgesia on colonic motility and patients’ outcome in colorectal surgery: a retrospective study - Abut, Yesim Cokay; Okan, Ismail; Tezer Kartal, Hayal; Ozdamar, Melih; Aldemir, Tayfun (Gastroenterology Review/Przegląd Gastroenterologiczny, 2011)
Aim : To explore the hypothesis that epidural medication stimulates colonic motility, shortens hospital stay and causes fewer complications than general anaesthesia alone, we conducted a retrospective study on patients undergoing colorectal surgery. Material and methods : Sixty-two adult patients who underwent colectomy or proctocolectomy at Vakif Gureba Training Hospital between June 2006 and December 2008 were divided into two groups retrospectively: an general anaesthesia only group (group 1) and a combined epidural and general anaesthesia group (group 2). First faecal and gas discharge time, first mobilization time, length of hospital stay and postoperative complications in 30 days after surgery were obtained from patients’ medical records. Results : Between the patients in the two groups matched and found similar for preoperative characteristics, there were no differences for gas and faecal discharge time, mobilization time, length of hospital stay or complications.